(untitled) (Patan Pragya, 2025)
This research paper investigates the contemporary condition of maternal health among pregnant women in Nepal by integrating recent national surveys, governmental reports, and scholarly research. The study aims to explore the relationship between anemia and pregnancy. The impact analysis is the approach in this paper. Critical indicators assessed encompass maternal mortality, antenatal care (ANC) coverage, institutional deliveries, nutritional status (including anemia and under-nutrition), as well as disparities based on geographic and socio-economic factors. Nepal has achieved significant advancements in maternal health—there has been an increase in facility-based births and skilled ANC coverage—however, considerable obstacles persist: the national maternal mortality ratio (MMR) exceeds the targets set by the Sustainable Development Goals, ongoing issues with anemia and micronutrient deficiencies, regional inequalities (with notably elevated MMR in certain provinces), and suboptimal outcomes for populations in remote and marginalized communities. The manuscript concludes with strategic policy and programmatic suggestions aimed at expediting equitable enhancements in maternal nutrition, the quality of ANC, and the incorporation of mental health screening within maternal healthcare services. The study has been undertaken based on secondary sources of information to examine the impact of socio-economic conditions and socio-cultural realities on the health of pregnant women in Nepal.